Self-Management Education to improve self-efficacy in Diabetes Millitus Patients Type II - Ayu Putri Ariani Gusti; Ratnawa Ratnawa; Kartin L Buheli (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Riskesdas 2018 data records that every year there is an increase in people with Diabetes Mellitus in Indonesia. Of the 35 provinces in Indonesia, Gorontalo Province ranks 7th in the number of people with Diabetes Mellitus with a prevalence that increased from 1.3% in 2013 to 2.4% in 2018 Indonesia ranks 6th out of ten countries with the highest number of diabetes patients. , which is 10.3 million patients per year 2017 and is expected to increase to 16.7 million patients per year 2045. Good diabetes management is expected to minimize the incidence of various microvascular and macrovascular complications. Therefore, someone diagnosed with DM must carry out self-management so that it can reduce the risk of complications. Several factors that influence the implementation of self-management in DM patients, one of which is self-efficacy. The number of cases of Diabetes Mellitus in the working area of the Kabila Bone Bolango Health Center was recorded at 120 cases. II. The Methods: This community service uses 30 people with diabetes mellitus who are registered in the prolanis who are in the working area of the Kabila Health Center. Activities include measuring blood sugar, body weight, pre-test and post-test of self-efficacy using a questionnaire adopted from the Management Self Efficacy Scale and intervention by providing education on intervention therapy based on the 4 pillars of diabetes management. This activity will be held in September-November 2021. The Results: Diabetes mellitus self-management education increased the selfefficacy of patients with sufficient categorical scores by 50% and good at 50% pretest and became sufficient 26% and good 74% and decreased the average blood sugar score for 3 stages.